Minimal Residual Disease Assessment in Multiple Myeloma Patients: Minimal Disease With Maximal Implications - Charalampous, Charalampos; Kourelis, Taxiarchis (Frontiers in Oncology, 2022)
Multiple Myeloma (ΜΜ), the second most common hematologic malignancy, has been the target of many therapeutic advances over the past two decades. The introduction of novel agents, such as proteasome inhibitors, immunomodulatory drugs, and monoclonal antibodies, along with autologous hematopoietic stem cell transplantation (ASCT) in the current standard of care, has increased the median survival of myeloma patients significantly. Nevertheless, a curative treatment option continues to elude us, and MM remains an incurable disease, with patients relapsing even after achieving deep conventionally defined responses, underscoring the need for the development of sensitive methods that will allow for proper identification and management of the patients with a higher probability of relapse. Accurate detection of Minimal Residual Disease (MRD) from a bone marrow biopsy represents a relatively new approach of evaluating response to treatment with data showing clear benefit from obtaining MRD(-) status at any point of the disease course. As life expectancy for patients with MM continues to increase and deep responses are starting to become the norm, establishing and refining the role of MRD in the disease course is more relevant than ever. This review examines the different methods used to detect MRD and discusses future considerations regarding the implementation in day-to-day clinical practice and as a prospective primary endpoint for clinical trials.